Code Mixing in Boy William’s Vlog “Kediaman Raja Film Indonesia” - Putu Wahyu Ananda Kusuma (Universitas Pendidikan Ganesha, 2023)
The code mixing phenomenon is a common practice in multilingual societies where individuals use more than one language or code in their daily conversations. The use of code mixing is also widely used by artists or public figures on various platforms. This can affect the use of code mixing. This study is aimed to analyze the types, motives, and reasons of the use of code mixing in Boy William’s Vlog. The data were collected by using documentation method and note taking technique. The data were analyzed by using qualitative method. In this case, the analyzed data types were classified by the theory of code mixing types, then the motives and reasons of the code mixing were identified by using the theory from Hockett (1958) to identify motives and Hoffman (1991) to identify the reason of code mixing. The data were presented informally. The result showed that there were found all the types of code mixing, all motives and six reasons, almost every reason for code mixing appears in the Boy William’s vlog, except being emphatic about something. There are three types of code mixing found in the expression of Boy William. Intra-sentential code mixing is the most frequent type of code mixing. Prestige filling motive is the most frequent type of motive that occurred in the code mixing. Talking about particular topic is the most frequent reason of the code mixing.